IMPROVING THE PROCESS AND OUTCOMES OF SCIENCE LEARNING IN GRADE VI USING THE INQUIRY METHOD AT STATE ELEMENTARY SCHOOL 178/II PURWASARI : PENINGKATAN PROSES DAN HASIL BELAJAR IPAS KELAS VI DENGAN MENGGUNAKAN METODE INKUIRI DI SD NEGERI 178/II PURWASARI - Subhanadri; Apdoludin; Erwindy Nurmeita Sari (SOSIOEDUKASI, 2025)
This study aims to improve the process and learning outcomes of Natural and Social Sciences (IPAS) through the application of inquiry learning methods to sixth grade students of SD Negeri 178/II Purwasari in the 2024/2025 academic year. The background of this study is the low student engagement and the results of learning in IPAS that have not yet reached the Learning Objectives Achievement Criteria (KKTP). The study uses a Classroom Action Research (CAR) approach which is implemented in two cycles, each consisting of two meetings with a duration of 2 × 35 minutes. The subjects of the study were 21 students, consisting of 10 male students and 11 female students. Data were collected through teacher performance observation sheets, student activity observation sheets, and cognitive learning outcome tests, then analyzed descriptively quantitatively. The results of the study showed a significant increase in each observed aspect. Teacher performance increased from 57.5% in the first cycle of the first meeting to 72.5% in the second meeting, and in the second cycle it increased to 75% in the first meeting and 85% in the second meeting. Student activity increased from 52.5% in the first meeting of cycle I to 61.9% in the second meeting, and in cycle II it reached 73.7% in the first meeting and 88.7% in the second meeting. The completion of cognitive learning outcomes also increased from 57.1% (12 students) in cycle I to 90.5% (19 students) in cycle II. These results prove that the application of the inquiry method is effective in increasing student engagement and science learning outcomes, and successfully meets the established success indicators.